Persistence of radiation-induced aberrations in patients after radiotherapy with C-ions and IMRT - Hartel, Carola Sabine; Nikoghosyan, Anna; Debus, Jürgen (Clinical and translational radiation oncology, 2018)
Background and purpose - Chromosomal aberrations in peripheral blood lymphocytes are a biomarker for radiation exposure and are associated with an increased risk for malignancies. To determine the long-term cytogenetic effect of radiotherapy, we analyzed the persistence of different aberration types up to 2.5years after the treatment. - Materials and methods - Cytogenetic damage was analyzed in lymphocytes from 14 patients that had undergone C-ion boost+IMRT treatment for prostate cancer. Samples were taken immediately, 1year and 2.5years after therapy. Aberrations were scored using the multiplex fluorescence in situ hybridization technique and grouped according to their transmissibility to daughter cells. - Results - Dicentric chromosomes (non-transmissible) and translocations (transmissible) were induced with equal frequencies. In the follow-up period, the translocation yield remained unchanged while the yield of dicentrics decreased to ≈40% of the initial value (p=0.011 and p=0.001 for 1 and 2.5years after compared to end of therapy). In 2 patients clonal aberrations were observed; however they were also found in samples taken before therapy and thus were not radiotherapy induced. - Conclusion - The shift in the aberrations spectrum towards a higher fraction of translocations indicates the exposure of hematopoietic stem and progenitor cells underlining the importance of a careful sparing of bone marrow during radiotherapy to minimize the risk for secondary cancers.
Gesehen am 16.09.2019